Cyanide Toxicity to Burkholderia cenocepacia Is Modulated by Polymicrobial Communities and Environmental Factors - Bernier, Steve P.; Workentine, Matthew L.; Li, Xiang; Magarvey, Nathan A.; O'Toole, George A.; Surette, Michael G. (Frontiers in Microbiology, 2016)
Microbes within polymicrobial communities can establish positive and negative interactions that have the potential to influence the overall behaviour of the community. Pseudomonas aeruginosa and species of the Burkholderia cepacia complex (Bcc) can co-exist in the lower airways, however several studies have shown that P. aeruginosa can effectively kill the Bcc in vitro, for which hydrogen cyanide was recently proposed to play a critical role. Here we show that modification of the environment (i.e. culture medium), long-term genetic adaptation of P. aeruginosa to the cystic fibrosis (CF) lung, or the addition of another bacterial species to the community can alter the sensitivity of Burkholderia cenocepacia to P. aeruginosa toxins. We specifically demonstrate that undefined rich media leads to higher susceptibility of B. cenocepacia to P. aeruginosa toxins like cyanide as compared to a synthetic medium (SCFM), that mimics the CF lung nutritional content. Overall, our study shows that the polymicrobial environment can have profound effects on negative interactions mediated by P. aeruginosa against B. cenocepacia. In fact, evolved P. aeruginosa or the presence of other species such as Staphylococcus aureus can directly abolish the direct competition mediated by cyanide and consequently maintaining a higher level of species diversity within the community.